2001
DOI: 10.1054/bjoc.2001.1931
|View full text |Cite
|
Sign up to set email alerts
|

Non-melanoma skin cancers and glucocorticoid therapy

Abstract: Organ transplant recipients taking immunosuppressive drugs are at an estimated 65-fold greater risk of squamous cell carcinoma (SCC) and a 10-fold higher risk of basal cell carcinoma (BCC) (McCann, 1999). Agents used to prevent allograft rejection include cyclosporine or azathioprine, often combined with glucocorticoids. Systemic glucocorticoids alone (e.g., prednisone, prednisolone, dexamethasone and cortisone) are widely used for a variety of medical conditions including connective tissue diseases, musculosk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
102
2
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 17 publications
6
102
2
5
Order By: Relevance
“…Further, we retrieved prescriptions for oral glucocorticoids from the Prescription Database (ATC codes in Appendix 1), as the use of these drugs has been associated with an increased risk of skin cancers (Karagas et al, 2001;Sorensen et al, 2004) and could be a potential confounder in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Further, we retrieved prescriptions for oral glucocorticoids from the Prescription Database (ATC codes in Appendix 1), as the use of these drugs has been associated with an increased risk of skin cancers (Karagas et al, 2001;Sorensen et al, 2004) and could be a potential confounder in our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For artificial sources of UVR, dermatological patients treated with phototherapy consisting of oral 8-methoxypsoralen plus UVA irradiation (PUVA) show a strong dose-response relationship for the risk of SCC, while that for BCC is less persuasive. A recent study of NMSC and artificial tanning devices found an association for both SCC and BCC (Karagas et al, 2002). Epidemiological studies of SCC of the lip provide evidence for a causal role for the cumulative exposure to UVR, although account must be taken of tobacco smoking (especially in pipes), which acts in synergy with UVR.…”
Section: Ultraviolet Radiationmentioning
confidence: 99%
“…Two recent studies conducted in Denmark and the USA reported increased risks of skin cancer and NHL among users of systemic glucocorticoids who were not transplant recipients. In both studies, use of glucocorticoids was associated with a two-fold increased risk of SCC and NHL, and a modestly increased risk of BCC (Karagas et al, 2001;Sorensen et al, 2004). However, two recent Swedish studies have questioned whether these associations were causal (Askling et al, 2005;Baecklund et al, 2006).…”
mentioning
confidence: 98%